Islamic Family Education in Developing Early Childhood Literacy: A Study of Parental Involvement in an Islamic Elementary School - Indrawati Amrullah Tajrin; Lina Revilla Malik; Syarifah Kurniaty Kahar; Muhammad Asrul Sultan (Borneo International Journal of Islamic Studies, 2026)
Biliteracy development during early childhood is increasingly recognized as an important educational goal in multilingual societies. While previous studies have highlighted the role of parental involvement in supporting children's literacy development, limited research has examined these practices through the lens of Islamic Family Education. This study investigates how Islamic Family Education is implemented through parental involvement and explores its contribution to early childhood biliteracy development in an Islamic elementary school. Employing a qualitative case study design, the research was conducted at an Islamic elementary school in Indonesia involving 52 first-grade students and their parents. Data were collected through biliteracy assessments, including Running Records, Deep Dive, Translanguaging, and Dictation Tasks, as well as semi-structured interviews with parents. The findings reveal that Islamic Family Education was enacted through literacy habituation, educational assistance and supervision, language support, and the creation of literacy-supportive home environments. These practices provided children with continuous opportunities to engage in literacy and bilingual learning beyond formal schooling. Assessment results showed that most students had reached the emergent biliteracy stage, with reading fluency representing the strongest dimension of biliteracy development, while translanguaging remained the most challenging. The study further demonstrates that parental involvement contributed to children's reading fluency, comprehension, vocabulary acquisition, phonological awareness, and emerging bilingual competencies. Theoretically, the study extends biliteracy research by conceptualizing parental involvement as an enactment of Islamic Family Education rather than merely a home literacy practice. It concludes that biliteracy development can be understood as an educational outcome of family-based Islamic educational practices and parental tarbiyah.